Single Nostril - A New Finding in the Phenotypic Spectrum of Schinzel Giedion Syndrome - Naher, Begum Sharifun; Shahid, ATM; Khan, Md Kamrul Ahsan; Nargis, Shahana; Hai, Abdul; Haque, Md Monimul (Bangladesh Journal of Child Health, 2010)
DOI: 10.3329/bjch.v30i1.6193 Bangladesh J Child Health 2005; Vol 29 (3): 111-113